STUDY OF AMINE-BASED CO2 CAPTURE TECHNOLOGY USING ANFIS AND ANN - ARIFFIN, ARIFF SYAZWAN (Universiti Teknologi PETRONAS, 2021)
The research is conducted to determine the best machine learning models that was developed using ANFIS and ANN algorithms for the study of CO2 capture technology using amine solvent.